2021
DOI: 10.1097/j.jcrs.0000000000000530
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of aerosol generation during cataract surgery

Abstract: Phacoemulsification cataract surgery was not found to be an aerosol-generating medical procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…This and the other studies of potential COVID-19 transmission during phacoemulsification provide persuasive evidence that cataract surgery is a relatively clean procedure with a low risk for microbial cross-contamination. [16][17][18][19][20][21] This would explain why strict enforcement of compulsory bans on reusing most ophthalmic surgical supplies and devices failed to produce a measurable benefit, while generating massive amounts of waste. 35,36 These registry studies do not scientifically establish that reusing ophthalmic surgical products is always safe and should be routinely adopted.…”
Section: Evidence and Opportunitymentioning
confidence: 99%
See 1 more Smart Citation
“…This and the other studies of potential COVID-19 transmission during phacoemulsification provide persuasive evidence that cataract surgery is a relatively clean procedure with a low risk for microbial cross-contamination. [16][17][18][19][20][21] This would explain why strict enforcement of compulsory bans on reusing most ophthalmic surgical supplies and devices failed to produce a measurable benefit, while generating massive amounts of waste. 35,36 These registry studies do not scientifically establish that reusing ophthalmic surgical products is always safe and should be routinely adopted.…”
Section: Evidence and Opportunitymentioning
confidence: 99%
“…However, multiple studies prompted by the COVID-19 pandemic concluded that the risk for crosscontamination from aerosolized pathogens during phacoemulsification is exceedingly remote. [16][17][18][19][20][21] This underscores the need for more research to ascertain which universal infection control policies do or do not lower the endophthalmitis risk.…”
mentioning
confidence: 99%
“…Fortunately, the two primary approaches for refractive surgery, corneal and lens-based, do not appear to be high risk procedures based on the lack of particle aerosolization. 7,8 This is also great news for our field because we can continue to offer refractive surgery options knowing that the risk of transmission through surgery appears to be extremely low.…”
Section: E D I T O R I a Lmentioning
confidence: 99%